2019
DOI: 10.1111/ecog.04325
|View full text |Cite
|
Sign up to set email alerts
|

Migratory shorebird adheres to Bergmann's Rule by responding to environmental conditions through the annual lifecycle

Abstract: The inverse relationship between body size and environmental temperature is a widespread ecogeographic pattern. However, the underlying forces that produce this pattern are unclear in many taxa. Expectations are particularly unclear for migratory species, as individuals may escape environmental extremes and reorient themselves along the environmental gradient. In addition, some aspects of body size are largely fixed while others are environmentally flexible and may vary seasonally. Here, we used a long‐term da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 62 publications
(106 reference statements)
1
22
0
Order By: Relevance
“…Being conceived for endotherms, where patterns coherent with such a prediction have been observed in a plethora of taxa in many regions of the globe (e.g. Ashton, 2002Ashton, , 2004Brown & Lee, 1969;Gibson et al, 2019;Meiri & Dayan, 2003;Olson et al, 2009;Rodríguez et al, 2006;Torres-Romero et al, 2016), recent studies have confirmed the validity of this biogeographical rule also in some ectotherms (e.g. Arnett & Gotelli, 1999;Ashton & Feldman, 2003;Chown & Gaston, 2010;Olalla-Tárraga & Rodríguez, 2007;Olalla-Tárraga et al, 2006;Pallarés et al, 2019).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Being conceived for endotherms, where patterns coherent with such a prediction have been observed in a plethora of taxa in many regions of the globe (e.g. Ashton, 2002Ashton, , 2004Brown & Lee, 1969;Gibson et al, 2019;Meiri & Dayan, 2003;Olson et al, 2009;Rodríguez et al, 2006;Torres-Romero et al, 2016), recent studies have confirmed the validity of this biogeographical rule also in some ectotherms (e.g. Arnett & Gotelli, 1999;Ashton & Feldman, 2003;Chown & Gaston, 2010;Olalla-Tárraga & Rodríguez, 2007;Olalla-Tárraga et al, 2006;Pallarés et al, 2019).…”
Section: Introductionmentioning
confidence: 75%
“…Ashton et al, 2002;Ashton, 2004;Blackburn et al, 2019;Blackburn & Ruggiero, 2001;Meiri, 2011;Meiri & Dayan, 2003;Olson et al, 2009) and at the within-species level on a continental geographical scale (e.g. Fan et al, 2019;Gibson et al, 2019;Graves, 1991;James, 1970;Jones et al, 2005). However, comprehensive intraspecific analyses on cosmopolitan taxa are almost null (but see Murphy, 1985).…”
Section: In Birds Geographical Variation In Body Size Compatible Withmentioning
confidence: 99%
“…Previous tests of Bergmann's rule have come to inconsistent conclusions when focusing on migratory organisms, with some taxa displaying weak or no adherence (Ashton, 2002; Collins et al., 2017) and others exhibiting adherence across breeding (e.g., Jones et al., 2005) and nonbreeding distributions (e.g., Gibson et al., 2019). The occurrence of the latitude‐body mass cline nearly immediately after hatching that we observed in prothonotary warblers provides a unique perspective that may help explain some of these inconsistencies observed in migratory species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many migrants (e.g., Nearctic‐Neotropical avian species) typically only encounter temperate environments during a relatively short breeding season, which may not represent a strong enough selective pressure for this pattern to become established. Thus, because of this putative lack of a strong evolutionary mechanism, and the possibility that multiple mechanisms contribute to latitudinal variation in size (Blackburn et al., 1999), adherence to Bergmann's rule may be considered paradoxical in migratory species and has been understudied (but see Collins, Relyea, Blustein, & Badami, 2017; Gibson et al., 2019; Jones et al., 2005; Van Buskirk, Mulvihill, & Leberman, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation